IMPLEMENTASI MANAJEMEN KONFLIK DALAM KEBIJAKAN SEKOLAH ADIWIYATA - Wiryatmo, Rahmat Dhoni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2022)
Environmental problems are becoming the concern for all of us, as well as in managing clean and green schools. However, in its implementation, there must be pros and cons in an institution. This study is aiming at analysing the implementation of conflict management in actualizing the “Adiwiyata” school program in SMP Negeri 2 Banyubiru, Semarang Regency. As a principle, it is a requirement for having respectable abilities to manage conflicts among the staffs in the institution so as to achieve the goal, i.e.: being able to bring about the clean and green school and for the most part, having successful in obtaining the predicate of “Adiwiyata” school. In this research, the writer used the interview and document study method for collecting the data in order to get the actual and factual information in relation with conflict management in implementing the “Adiwiyata” school program. The data analysis technique used in this study is based on the Miles and Huberman model. The result of the study showed that the principle is able to overcome the conflicts arouse as the response of implementing the program of “Adiwiyata” school by means of flexible approach. If the conflict is functional, then the principal takes a neutral approach with compromise, collaboration, and negotiation (no party wins and losses) and if it is dysfunctional, she takes a win-lose approach by forcing, given the urgency of the problems that cause conflict.